(3WHb GdMdhi hUMGa Gdef hGdSdhis - (3YHO Gddg Hf Ydj Hf CMeO Hf eMeO GdMSfj, GdeYQha HGdhRjQ,J (B1147 (3g` s ((3ebHd Hf YHOg Hf Ydi Hf YHOGddg s)
(3BNQgG (B:s
(3eVi CMeO bOhg GdYGQajf cQje GdfLGQ YOje GdfXjQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B86s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B399 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B199 s
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT HJfg (B(2313) s
Keywords: (3GdJGQjNs